Bursting Smoke as an Infrared Countermeasure - Singh, Amarjit; Kamale, P. J.; Joshi, S. A.; Bankar, L. K. (Defence Science Journal, 2013)
This paper describes the experimental setup for the evaluation of bursting smoke for anti-infrared role using SR-5000 spectroradiometer and a source of IR radiation (8-13 micrometer) using cadmium-mercury-telluride (CMI) detector cooled by liquid nitrogen. The particle size and shape of the powders used in the bursting smokes were determined microscopically using Carl Zeiss Jena Neophot- 21. Highest attenuation of 97 -lOO percent was produced for about 12 s using a mixture of bronze flakes and chaff, and for about 8 s using a mixture of bronze copper lined flakes, bronze flakes and chaff.